In the Beginning Was the Hand: Ernst Kapp and the Relation Between Machine and Organism [en el Principio Era la Mano: Ernst Kapp y la Relación Entre Máquina y Organismo] - Esposito-Varriale, M (University of Valparaiso, 2019)
The relation between organisms and machines is very old. Over a century ago, the French historian and philosopher Alfred Victor Espinas observed that from the Greeks onwards the intelligibility of the organic world presupposed a comparison with technical objects. Aristotle, for instance, associated living organs with mechanical artefacts in order to understand animals movements. In the modern period, Descartes, Borelli and other mechanists defended the idea that organisms are, in reality, machines. Today, philosophers and scientists still argue that the genome is like a software and the brain is like a computer. In this article I reconsider the relation between organisms and machines from the perspective of the German geographer and philosopher Ernst Kapp (1808-1896), one of the founding fathers of the Philosophy of Technology. Breaking with a long and venerable philosophical tradition, Kapp argued that machines are, in reality, "organic projections". Organisms are not machines; they are an imitation or reflection of the organic world. First of all, I clarify the hypothesis of "organic projection" (including its virtues and limits). Secondly, I consider some of the philosophical consequences that such a hypothesis entails over the debate between machinists and anti-mechanists. Finally, and following the previous considerations, I defend the importance of reconnecting the philosophy of technology with philosophy of biology in order to better understand the development of contemporary biology. © 2019 Instituto de Filosofía, Universidad de Valparaíso.